EPIDEMIOLOGI DAN FAKTOR RISIKO PENYAKIT ARTERI PERIFER: TINJAUAN DARI POPULASI GLOBAL DAN ASIA DENGAN PERBANDINGAN PANDUAN KLINIS - Melya Susanti (Nusantara Hasana Journal, 2025)
Peripheral artery disease (PAD) is a systemic manifestation of atherosclerosis that significantly contributes to increased morbidity and mortality, and reduced quality of life. Globally, the burden of PAD shows an increasing trend, with the highest prevalence among the elderly, those with diabetes mellitus, hypertension, dyslipidemia, and those with smoking habits. Global Burden of Disease data demonstrates regional variations in distribution, with Asia displaying distinct sociodemographic determinants and diagnostic challenges. In countries like Indonesia, limited epidemiological data and high underdiagnosis rates remain major barriers to early detection. In addition to the main risk factors, a number of new determinants, including nutritional and lifestyle patterns, exposure to air pollution, chronic inflammation, and genetic predisposition, further exacerbate the disease course. Severe complications, particularly limb-threatening ischemia, are closely associated with coronary artery and cerebrovascular disease, ultimately worsening clinical outcomes in patients with polyvascular disease. This study is a literature review examining international and national publications indexed in Scopus, PubMed, and Sinta within the last five years, as well as the latest clinical guidelines (ESC 2024, ACC/AHA 2024, ESVS 2024). Literature selection was based on relevance to epidemiology, risk factors, clinical implications, and comparability of PAD management guidelines. Global strategies for PAD management generally demonstrate uniformity, although approaches differ in specific populations. Research gaps include limited data in Southeast Asia and a lack of genetic studies in non-European populations. Adapting international guidelines to the local context is essential to more effectively reduce the burden of PAD in the Asian region.